Actividad contra Trypanosoma cruzi (Kinetoplastida: Trypanosomatidae) de extractos metanólicos de plantas de uso medicinal en México - Pérez Treviño, Karla Carmelita; Galaviz, Lucio; Iracheta Villarreal, Jesús Mario; Lucero Velasco, Eliud Alonso; Molina Garza, Zinnia Judith (2017)
Abstract: Activity against Trypanosoma cruzi (Kinetoplastida: Trypanosomatidae) of methanolic extracts of medicinal use plants in Mexico. American trypanosomiasis is a potentially lethal disease caused by the hemoflagellate protozoan Trypanosoma cruzi. This neglected disease affects from 6 to 7 million people worldwide. Currently there are only two medicines to treat this disease: beznidazol and nifurtimox, both effective if they are administrated in the acute phase of infection, although their effectiveness fades away in the chronic phase; it also induces significant side effects. The aim of this study is to screen the trypanocidal activity of methanolic extracts from Hematoxilum brasiletto, Marrubium vulgare, Schinus molle, and Cympongon citratus, against T. cruzi epimastigotes, followed by the chromatographic separation, and identification of active compounds of the best candidate by colored chemical reactions; furthermore, it was also determined their cytotoxic effect in human lymphocytes and the brine shrimp Artemia salina. The extract of H. brasiletto showed the highest anti-T. cruzi activity with a inhibitory concentration (IC50) of 543 µg/mL; in descending order, it was followed by M. vulgare (IC50 = 647 µg/mL), S. molle (IC = 827 µg/mL) and finally, C. citratus (IC = 1 210 µg/mL). The chromatographic fraction Fr22 from H. brasiletto showed the best anti-T. cruzi effectivity (IC50 = 0.238 mg/mL), when compared to the other fraction or the whole extract, with no cytotoxic effect against human lymphocytes or A. salina. The active compounds were identified as tannins, quinones, flavonoids and sesquiterpenlactones. In conclusion, active compounds against T. cruzi were identified for the first time in H. brasiletto, with non-cytotoxic effects. The H. brasiletto extract, according to our results, could be used as an alternative treatment for the Chagas disease; however, additional studies will be necessary to test their activity and doses in a murine model, with the complete identification of the active compounds, on which we are investigating. Rev. Biol. Trop. 65 (4): 1459-1469. Epub 2017 December 01. Key words: Trypanosoma cruzi, Haematoxylum brasiletto, medicinal plants, methanolic extracts.